1990
DOI: 10.1111/j.1476-5381.1990.tb12731.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C‐mediated contractile responses of arteries from diabetic rats

Abstract: 1 The role of protein kinase C (PKC) in mediating enhanced contractile responses of aortae and mesenteric arteries from male rats with 12-14 week streptozotocin-induced diabetes to noradrenaline (NA) was investigated using the PKC activator, phorbol 12,13-dibutyrate (PDB), and the PKC inhibitor, staurosporine. 2 Maximum contractile responses of aortae and mesenteric arteries from diabetic rats to NA were significantly enhanced compared with responses of arteries from age-matched control animals. The maximum N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 39 publications
3
33
2
Order By: Relevance
“…1), compared with exposure to continuous normal glucose or high glucose. The markers chosen were: (1) the basement membrane protein fibronectin, shown to be overexpressed in the vessels of diabetic patients [23]; (2) the signalling kinase PKC-β, stimulated by high glucose through a cofactor, diacylglycerol [24,25]; (3) the mitochondrial pro-apoptotic protein BCL-2 family member Bax, indicative of mitochondrial stress [26] and associated with vascular diabetic complications [27]; (4) the DNA damage protein PAR, a product of PARP, shown to be a critical factor in the development of vascular diabetic complications [7]; (5) p47phox, an inducible subunit of the enzyme NAD(P)H oxidase, shown to be a source of ROS in the endothelium of diabetic patients [28]; and (6) the protein adduct 3-NY, a marker of oxidative stress and vascular diabetic complications [29][30][31][32]. As has been shown previously, chronic high glucose resulted in significantly increased levels of: fibronectin [10]; phospho-(activated) PKC-α/βII [25]; p47phox [33]; and 3-NY [31], while the increase in Bax was not statistically significant [27] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1), compared with exposure to continuous normal glucose or high glucose. The markers chosen were: (1) the basement membrane protein fibronectin, shown to be overexpressed in the vessels of diabetic patients [23]; (2) the signalling kinase PKC-β, stimulated by high glucose through a cofactor, diacylglycerol [24,25]; (3) the mitochondrial pro-apoptotic protein BCL-2 family member Bax, indicative of mitochondrial stress [26] and associated with vascular diabetic complications [27]; (4) the DNA damage protein PAR, a product of PARP, shown to be a critical factor in the development of vascular diabetic complications [7]; (5) p47phox, an inducible subunit of the enzyme NAD(P)H oxidase, shown to be a source of ROS in the endothelium of diabetic patients [28]; and (6) the protein adduct 3-NY, a marker of oxidative stress and vascular diabetic complications [29][30][31][32]. As has been shown previously, chronic high glucose resulted in significantly increased levels of: fibronectin [10]; phospho-(activated) PKC-α/βII [25]; p47phox [33]; and 3-NY [31], while the increase in Bax was not statistically significant [27] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PKC and phospholipids generated by calcium-activated phospholipase A 2 (cPLA 2 ) regulate several vascular functions such as cell growth, permeability, contractility, and extracellular matrix protein synthesis. In diabetes, activation of PKC induces an increase in vascular smooth muscle contractility (40) and expression of NADPH oxidase, resulting in ROS generation (42) and decreased Na + ,K + -ATPase activity (49). However, we have recently reported that diabetic aorta is also associated with increased Na + ,K + -ATPase activity, an effect, which is also mediated by PKC (50).…”
Section: Endothelial Dysfunction In Diabetes Mellitusmentioning
confidence: 99%
“…Although the nature of the pathogenic link between elevated circulating levels of glucose and cardiovascular complications is a source of debate, it is clearly recognized that hyperglycemia is responsible for the pathogenesis of vascular complica- tions associated with DM. It has been demonstrated that acute or chronic hyperglycemia can cause several changes in vascular function, including a decrease in endotheliumdependent relaxation (37)(38)(39), an increased contractile response of vascular smooth muscle (38,40,41) and a predisposition to the development of inflammatory, thrombotic and atherosclerotic events (42). The progression of vascular disease in DM is largely related to endothelial dysfunction mechanisms.…”
Section: Endothelial Dysfunction In Diabetes Mellitusmentioning
confidence: 99%
“…Additionally, there is a large body of evidence demonstrating that [Ca 2ϩ ] i is elevated in vascular smooth muscle cells obtained from hypercho-lesterolemic and diabetic models, both animal and human (9,30,47,67,72). Although many investigators have shown diabetes-induced increases in vasoreactivity of several different vascular tissue beds (1)(2)(3)53), the effect of diabetes on K ϩ channel activity or expression, Ca 2ϩ regulation, and vascular smooth muscle reactivity has not been thoroughly studied. A better understanding of this relationship could help explain the enhanced vascular reactivity to agonists and elucidate potential therapeutic targets for the treatment of altered vascular reactivity.…”
Section: Camentioning
confidence: 99%